Bisecting N-Acetylglucosamine on EGFR Inhibits Malignant Phenotype of Breast Cancer via Down-Regulation of EGFR/Erk Signaling - Cheng, Lanming; Cao, Lin; Wu, Yurong; Xie, Wenjie; Li, Jiaqi; Guan, Feng; Tan, Zengqi (Frontiers in Oncology, 2020)
Glycosylation, the most prevalent and diverse post-translational modification of protein, plays crucial biological roles in many physiological and pathological events. Alteration of N-glycan has been detected during breast cancer progression. Among the specific N-glycan structures, bisecting N-Acetylglucosamine (GlcNAc) is a β1,4-linked GlcNAc attached to the core β-mannose residue, and is catalyzed by glycosyltransferase MGAT3. Bisecting GlcNAc levels were commonly dysregulated in different types of cancer. In this study, we utilized mass spectrometry and lectin microarray analysis to investigate aberrant N-glycans in breast cancer cells. Our data showed the decreased levels of bisecting GlcNAc and down-regulated expression of MGAT3 in breast cancer cells than normal epithelial cells. Using PHA-E (a plant lectin recognizing and combining bisecting GlcNAc) based enrichment coupled with nanoLC-MS/MS, we analyzed the glycoproteins bearing bisecting GlcNAc in various breast cancer cells. Among the differentially expressed glycoproteins, levels of bisecting GlcNAc on EGFR were significantly decreased in breast cancer cells, confirmed by immunostaining and immunoprecipation. We overexpressed MGAT3 in breast cancer MDA-MB-231 cells, and overexpression of MGAT3 significantly enhanced the bisecting N-GlcNAc on EGFR and suppressed the EGFR/Erk signaling, which further resulted in the reduction of migratory ability, cell proliferation, and clonal formation. Taken together, we conclude that bisecting N-GlcNAc on EGFR inhibits malignant phenotype of breast cancer via down-regulation of EGFR/Erk signaling.